The city in urban poverty - Lemanski, Charlotte, 1977-; Marx, Colin, 1967- (EADI global development., 2015)
The authors respond to the absence of critical debate surrounding the spaces of the city in urban poverty research and policy. While existing research interprets the urban as a static container or empty backdrop for urban poverty processes, the chapters in this book critically explore the active role played by the spaces of the city in shaping and perpetuating urban poverty. Scholars and policymakers from a range of disciplinary perspectives use historic and contemporary examples from Asia, Africa and Latin America to demonstrate the ways in which urban poverty does not just exist in the spaces of the city, but that the city itself is also in urban poverty. So the city is both in and of urban poverty (and vice versa). Attending to the way that spaces of cities are part of the processes that reproduce and perpetuate exploitation and inequality sheds additional light on the dynamics of poverty for researchers and policy makers.